2013
DOI: 10.5539/emr.v2n1p98
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Organizational Factors of Safe Behaviour among Ghanaian Industrial Workers

Abstract: The aim of this study is to compare individual and organizational factors as predictors of accident frequency. Four hypotheses based on the literature were presented: 1) both individual and organizational factors contribute to accident frequency, 2) individual factors have more impact than organizational factors, 3) both Organizational citizenship behaviour and Perceived organizational support are positively associated with safety behaviour, and 4) among the four organizational factors, Perceived organisationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The relationship between occupational accidents and OCB was not established in this study. However, other researchers reported significant correlation between organizational citizenship behavior and accidents (46,47). The complexity and diversity of the responsibilities of nurses and huge amounts of labors can be mentioned as reasons for this difference.…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between occupational accidents and OCB was not established in this study. However, other researchers reported significant correlation between organizational citizenship behavior and accidents (46,47). The complexity and diversity of the responsibilities of nurses and huge amounts of labors can be mentioned as reasons for this difference.…”
Section: Discussionmentioning
confidence: 94%
“…In the literature on workplace safety, OST provides insight into how employees perceive and behave towards their workplace safety (e.g. Hofmann and Morgeson, 1999;Gyekye and Salminen, 2007;Salminen et al, 2013). OST emphasises that employees who perceive support in the organisation could have a felt obligation to return such support with positive work behaviours (Eisenberger et al, 1986;Rhoades and Eisenberger, 2002).…”
Section: Theoretical Background and Hypotheses Development Theoretical Perspectives Of Esbsmentioning
confidence: 99%
“…Because organisational support perceptions influence safety perceptions and subsequent safety behaviours at the workplace (e.g. Gyekye and Salminen, 2007;Salminen et al, 2013). The next section reviews other theories or literature towards the hypotheses development.…”
Section: Theoretical Background and Hypotheses Development Theoretical Perspectives Of Esbsmentioning
confidence: 99%
“…HHC is surrounded by multiple risk factors, such as physical, interpersonal, and psychosocial factors (Craven, Byrne, Sims-Gould, & Martin-Matthews, 2012). Evidences from safety researchers suggested that these risk factors can be effectively managed, thus promoting workplace safety (Richter, McAlearney, & Pennell, 2016;Salminen, Gyekye, & Ojajarvi, 2013). With regards the safety management, organizational support is positively affecting the employee behaviors (Nadim, Hassan, Abbas, Naveed,& 2016).…”
Section: Introductionmentioning
confidence: 99%